2011
DOI: 10.1002/clen.201000417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resuspension on the Release of Heavy Metals and Water Chemistry in Anoxic and Oxic Sediments

Abstract: Two types of river sediments with contrasting characteristics (anoxic or oxic) were resuspended and the release of heavy metals and changes in water chemistry were investigated. During resuspension of the anoxic sediment, the dissolved oxygen (DO) concentration and redox potential of the water layer decreased abruptly within the first 1 min, followed by increases toward the end of the resuspension period. Heavy metals were released rapidly in the first 6 h, probably due to the oxidation of acid volatile sulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Resuspension of sediment to environmentally relevant SPM concentrations resulted in modest declines of pH and dissolved O 2 in overlying water. Other short‐term resuspension studies have reported pH changes similar to those observed here (typically <1.0 pH unit), but O 2 declines ranged from no change to anoxia . Decreases in pH and O 2 during the first few hours of resuspension, like those observed in the present study, have been attributed to aerobic respiration and oxidation of reduced inorganic ions and molecules (e.g., Fe 2+ , FeS); however, protons liberated during oxidation can be buffered by suspended sediment and overlying water .…”
Section: Discussionsupporting
confidence: 82%
“…Resuspension of sediment to environmentally relevant SPM concentrations resulted in modest declines of pH and dissolved O 2 in overlying water. Other short‐term resuspension studies have reported pH changes similar to those observed here (typically <1.0 pH unit), but O 2 declines ranged from no change to anoxia . Decreases in pH and O 2 during the first few hours of resuspension, like those observed in the present study, have been attributed to aerobic respiration and oxidation of reduced inorganic ions and molecules (e.g., Fe 2+ , FeS); however, protons liberated during oxidation can be buffered by suspended sediment and overlying water .…”
Section: Discussionsupporting
confidence: 82%
“…Several studies reported that heavy metal dissolution is redox dependent in an environment with low oxygen concentrations. [15,30] We measured oxygen in the stormwater ponds but found no connection between either oxygen concentrations and heavy metal retention or oxygen content and dissolved heavy metal concentration in the pond outlet (except for Ni where there was a significant correlation (p = 0.006)), for example, one pond with a low oxygen level (35.2%) removed more than 90% of Pb. Including the measured nitrate concentration as an additional oxidation potential did not improve the statistical power.…”
Section: Retention In the Pondsmentioning
confidence: 94%
“…The relative affinity of iron compounds for various metals is directly related to pH controls on speciation but is also dependent on the redox potential. Bacterial respiration utilizing these iron compounds has been demonstrated as a source of metal mobility when conditions turn from oxic to anoxic (Cantwell et al 2002;Cappuyns et al 2006;Hwang et al 2011;Monnin et al 2018). Resuspension may also affect the release and sequestration of metals depending on the initial sediment conditions.…”
Section: Discussionmentioning
confidence: 99%